Red Blood Cell Distribution Width Is Associated With Adverse Kidney Outcomes in Patients With Chronic Kidney Disease - Deng, Xinwei; Gao, Bixia; Wang, Fang; Zhao, Ming-hui; Wang, Jinwei; Zhang, Luxia (Frontiers in Medicine, 2022)
Background: Chronic kidney disease (CKD) is a global public health issue. Red cell distribution width (RDW) is a recently recognized potential inflammatory marker, which mirrors the variability in erythrocyte volume. Studies indicate that elevated RDW is associated with increased risk of mortality in CKD patients, while evidence regarding the impact of RDW on kidney outcome is limited. Methods: Altogether 523 patients with CKD stage 1-4 from a single center were enrolled. The time-averaged estimated glomerular filtration rate (eGFR) slope was determined using linear mixed effects models. Rapid CKD progression was defined by an eGFR decline > 3 ml/min/1.73m2/year. The composite endpoints were defined as doubling of serum creatinine, a 30% decline in initial eGFR or incidence of eGFR < 15 ml/min/1.73m2, whichever occurred first. Multivariable logistic regression or Cox proportional hazards regression was performed, as appropriate. Results: During a median follow-up of 26 (interquartile range [IQR]: 12, 36) months, 196 (37.48%) patients suffered a rapid CKD progression and 172 (32.89%) composite kidney events occurred at a rate of 32.3/100 patient-years in the high RDW group, compared with 14.7/100 patient-years of the remainder. The annual eGFR change was obviously steeper in high RDW group (-3.48 [95% confidence interval (CI): -4.84, -2.12] ml/min/1.73m2/year vs. -1.86 [95% CI: -2.27, -1.45] ml/min/1.73m2/year among those with RDW of >14.5% and ≤14.5%, respectively, P for between-group difference < 0.05). So was the risk of rapid renal function loss (odds ratio = 2.13, 95%CI: 1.19 - 2.81) and composite kidney outcomes (hazards ratio = 1.57, 95%CI: 1.06 - 2.33). The significant association remained consistent in the sensitivity analysis. Conclusions: Increased RDW value is independently associated with accelerated CKD deterioration. Findings of this study suggest RDW be used in risk stratification of CKD progression, whereas further studies are warranted to verify the association.